EDUCATIONAL PUBLIC-PRIVATE PARTNERSHIP: FACTORS, TERMS AND PROSPECTS - Berikbolova Ulzhan Doskalievna; Abdimomynova Almakul Shakirbekovna; Duzelbaeva Gulshat Berikbaevna; Beketova Kamar Nazarbekovna (Academic Journal of Physical and Chemical Sciences, 2020)
In terms of formation of a knowledge-based society, of an innovative economy development, the importance of education sector for the socio-economic development of the country significantly increases. The role in the modern society of the education sector is determined by the fact that competencies are formed in it, knowledge is created and disseminated - the key resources of modern society. The effectiveness of education sector functioning increasingly determines the success of socio-economic development. The concept of public-private partnership (PPP) has proven effective in applying its principles in such a socially significant sphere of the economy as education. Therefore, one of the priority tasks of the development of national education is to create conditions for formation of an effective partnership mechanism between representatives of business structures and educational institutions while providing economic support to educational institutions, managing the content of the educational process, as well as in terms of research activities. The relevance of this issue for the domestic economy is also due to the fact that in a crisis, the distinguishing features of which are financial and economic instability and insufficient budget funds attracted for the implementation of socially significant projects and programs, there is a need to form motivational incentives and create opportunities to attract extra-budgetary sources of financing, as well as other resources of the private sector. The article is devoted to the study of the advantages and disadvantages of PPPs, the search for mechanisms of business structures interaction with educational institutions and the state, adequate to modern conditions, as well as the preparation of recommendations on the trends and prospects for the development of this cooperation in the education sector.